Observações sobre a fundamentação moral do direito em Kant - Erick Calheiros de Lima (Ethic@: an International Journal for Moral Philosophy)
One could assert that the two main tasks of Kant´s philosophy of right are, firstly, to show that the community of external freedom must become positive as an enforced or coercive order, i.e as the submission of all arbitria to a juridical-political arrangement that is able to judge people and to punish infractions. This is conceptually achieved in the transition from the private right to the public sphere of justice, where Kant demonstrates the practical necessity of the self-institution of a political-public apparatus to regulate possible conflicts originated by the multiplicity of private juridical perspectives in the absence of supraindividual jurisdiction of the state – which Kant, based on his conception of practical reason, conceives as a practical ideal form of the “state of nature”. Furthermore, Kant´s theory aims to expose how the community of external freedom should be organized and maintained in conformity with reason, what brings him to the delineation of the ideal structure of the state as the norm for the positive laws, denominated “original contract”, the criterion of moral legitimacy of positive public laws and of the political justice, as well. This paper intends to show how these two main tasks, as far as they are assumed to be the fundamental goals of Kant´s theory of rights, appear to be articulated within the “Einleitung in die Rechtslehre” through the concepts “autorization to coerce” (Befugnis zu zwingen) and “moral capacity to place others under obligation” (moralischer Vermögen andere zu verplichten).